1984
DOI: 10.3168/jds.s0022-0302(84)81670-7
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Bile Tolerance of Lactobacillus acidophilus Used as a Dietary Adjunct

Abstract: Cultures of lactobacilli identified as Lactobacillus acidophilus from the intestinal contents of young calves varied in their ability to grow in broth containing .3% oxgall compared with control broth. Frozen concentrated cultures were prepared from a strain exhibiting low tolerance to bile and from a strain exhibiting high tolerance to bile. Plate counts were comparable from the concentrated cultures before and after frozen storage on lactobacilli MRS agar with and without .15% oxgall. In a feeding trial invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
203
1
19

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(235 citation statements)
references
References 12 publications
12
203
1
19
Order By: Relevance
“…In a similar study, a 38.5% inhibition by gastric juice from E. durans and 56.8% from E. faecium samples were observed, confirming the resistance to gastric pH by enterococci samples observed in the present study (Cueto-Vigil et al, 2010 According to Gilliland et al (1984), when 0.3 of absorbance is achieved after at least 8h of incubation at 37 0 C in presence of 0.3% oxgall, a microorganism can be considered tolerant or resistant to biliary salts. Considering this, 11 (68.75%) out of 16 samples tested can be considered tolerant to biliary salts (Table 4).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…In a similar study, a 38.5% inhibition by gastric juice from E. durans and 56.8% from E. faecium samples were observed, confirming the resistance to gastric pH by enterococci samples observed in the present study (Cueto-Vigil et al, 2010 According to Gilliland et al (1984), when 0.3 of absorbance is achieved after at least 8h of incubation at 37 0 C in presence of 0.3% oxgall, a microorganism can be considered tolerant or resistant to biliary salts. Considering this, 11 (68.75%) out of 16 samples tested can be considered tolerant to biliary salts (Table 4).…”
Section: Resultssupporting
confidence: 73%
“…According to Gilliland et al (1984), when a 0.3 absorbance is achieved after at least 2h of incubation at 37 o C in presence of gastric pH between 1.5 and 4.0, a microorganism can be considered tolerant or resistant to gastric pH. Considering this, 13 (81.25%) out of 16 samples tested can be considered tolerant to gastric pH (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The physiological concentration of human bile salts ranges 0.3-0.5% [23,24]. Considering bile tolerance an important characteristic of probiotic microorganisms, it has been reported that 0.3% oxgall closely appropriates the bile level of the human gastrointestinal tract, and the concentration of 0.3% bile salts has been considered crucial for screening and selection of human probiotics [25,26]. However, survival of lactobacilli at pH value of 3 for 2 h and at a bile concentration of 0.1% has also been considered optimal acid and bile tolerance for strains to be used as probiotics [27].…”
Section: Discussionmentioning
confidence: 99%
“…While sodium chloride is growth inhibitory to several other types of bacteria, the probiotic organisms withstand high salt concentration in the human gut [25]. The isolated Lactobacillus strains from yogurts tolerated 1-9% sodium chloride in the MRS broth, and all the isolates maintained good growth up to 3% concentration; growth declined with the increase of salt concentration in the broth [14].…”
Section: Translational Biomedicine Issn 2172-0479mentioning
confidence: 99%
“…It is considered that to produce beneficial effects in the host the bacteria used should be able to survive and grow in the gastrointestinal tract, resisting the gastric acids of the stomach and bile salts of the intestine [5,13]. Studies carried out by Noh and Gilliland [12] have shown that bile salts β-galactosidase des souches bile-tolérantes augmentait au cours de la croissance dans les milieux contenant 0,15 et 0,30 % d'oxgall.…”
Section: Introductionmentioning
confidence: 99%